Understanding the determinants of online repeat purchase intention and moderating role of habit: The case of online group-buying in Taiwan. Issue 1 (February 2015) - Hsu, Meng-Hsiang; Chang, Chun-Ming; Chuang, Li-Wen
Highlights A theoretical model integrating the literature of expectation–confirmation model, and online shopping was proposed. Increasing trust and satisfaction will facilitate repurchase intention. Habit exerts a moderating effect on the determinants of repeat purchase intention. Satisfaction has significant influence on trust. Perceived value, confirmation, and website quality are the predictors of satisfaction.